(untitled) (Open Herald: Periodical of Methodical Research, 2025)
Nephrotic syndrome (NS) represents a significant contributor to the incidence of end-stage renal disease, characterized by symptoms such as edema, proteinuria, hypoalbuminemia, and hyperlipidemia. The syndrome is intricately associated with alterations in the immune response. This research focused on analyzing the serum concentrations of immunoglobulins G (IgG), M (IgM), and A (IgA) in a cohort of Iraqi pediatric patients diagnosed with NS. Blood specimens were obtained from 75 children, aged 2 to 15 years, presenting with newly diagnosed typical NS. The study findings indicated a notable reduction in the average serum IgG level (438.18 mg/dL) among NS patients compared to healthy controls (954.09 mg/dL), alongside a significant elevation in the mean serum IgM level (185.66 mg/dL) relative to controls (111.73 mg/dL). Conversely, serum IgA levels exhibited no significant disparity between NS patients and healthy controls. In conclusion, this investigation underscores a marked association between immunological markers and nephrotic syndrome in Iraqi children. The assessment of immunoglobulin levels, coupled with clinical and biochemical parameters, plays a crucial role in the management of NS. There is increasing interest in extensive studies to demonstrate that low IgG and high IgM levels are sensitive markers of worse outcomes in pediatric patients with NS